Analisis Belanja Daerah pada Pemerintah Daerah Kabupaten Jepara - Agustiyana Lailatus Sholikhah; Nuwun Priyono (Jurnal Akuntansi, 2022)
This study aims to determine the magnitude of variance ratio analysis and regional spending compatibility ratio analysis in Jepara Regency Regional Government for the period 2017 to 2020. In addition, we also want to know the level of regional spending efficiency in Jepara Regency Regional Government. The research method used is quantitative descriptive by using the analysis of variance ratio analysis, compatibility ratio analysis, and spending efficiency ratio analysis. The results show that from 2017 to 2020 Jepara Regency Regional Government falls into the category of favorable variance performance because the realization of expenditure does not exceed the total budgeted, almost 70% of total regional expenditure is used for operating expenditure, while the proportion of capital expenditure is far from operating expenditure, and the performance of the Jepara Regency Regional Government are included in the efficient category. This shows that the Regional Government of Jepara regency has succeeded in spending efficiency. The Regional Finance and Assets Management Agency should pay more attention to the situation and conditions in the hope that the budget can be realized well.   Keywords: Regional Expenditure, Variance Ratio, Harmony Ratio, and Efficiency Ratio